Effects Of Family Size, Status And Taste On The Type Of Domestic Fuel Utilization In Kano Metropolis, Kano State; Nigeria - Lambu (PhD), Ibrahim Badamasi; Bashir, Muhammed Bello (Advances in Social Sciences Research Journal, 2016)
The paper explores the effect of family size, status and taste on the adoption of domestic fuel energy utilization in the metropolitan Kano. As a typical Islamic culture; polygamy is widely accepted among the community irrespective of economic status (rich and poor), political class (leaders and followers) as well as religious affiliation (sectarian and secular). The culture accelerates conpetitiion between co-wives for more children, sex preferences and marrieg security which consequently lead to large family size. Reasons and major causes are envisaged from which recommendations were tendered in order to reduce/cushione the impact on the environment. Both quantitative and qualitative data are used as well simple random sampling technique is adopted in handling the households for administration of questionnaire and interviews in the area. Interstingly, the study discovered that both monogamous and polygamous families have higher fertility and in average each family consist of eight children excluding the parents. The volume of the food for the extended family system is high hence need bigger source of energy to save time and monetary cost. Some held cultural taboos that food cooked by fuelwood is better than on cooker gas. Other reasons such as risk of fire outbreak scare some household from gas cooker. To save our ecosystem, Kerozine stoves, solar and electric cookers should be made available, affordable and accessable to all.